Mengapa tidak berperang? Norma Politik Luar Negeri Cina dan Konflik Laut Cina Selatan - Mohamad Rosyidin (Department of International Relations, Universitas Andalas)
South China Sea conflict is one of the most destabilizing factors in Southeast Asia. Despite it has occured for long time period, there has not been major wars among occupants. This puzzle challenges realist particularly ofense-defense theory stating that when perception of victory is greater than defeat, it will lead to war. China’s military capability is far greater than any contry in the region. Yet, China does not intent to attack others. Assumption that China is an offensive and hegemonic nation is not in accordance with reality. Material-based explanation cannot account for China’s foreign policy. This article seeks to explain why South China Sea conflict does not lead to war between occupants. Using constructivism in international relations, this article argues that China’s domestic norms of national security plays great role which constitute its foreign policy character. Norms of cooperative security or hezuo anquan which is rooted from Confucian culture emphasize on harmony and cooperation that generate self-restraint diplomacy. As a result, China would not employ its military power to solve South China Sea conflict. This article concludes that norms held by country constitute its interest and in turn guide state’s policy.